2017
DOI: 10.1016/j.ijrobp.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of IL-8 and TGF-β1 Predict Radiation-Induced Lung Toxicity in Non-Small Cell Lung Cancer: A Validation Study

Abstract: Purpose/Objectives We previously reported that combination of mean lung dose (MLD), and inflammatory cytokines (IL-8 and TGF-β1) may provide a more accurate model for radiation-induced lung toxicity (RILT) prediction in 58 patients with non-small cell lung cancer (NSCLC). This study is to validate the previous findings with new patients and explore new models with more cytokines. Materials/Methods 142 patients with stage I–III NSCLC treated with definitive radiation therapy (RT) from prospective studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…The risk factors for radiation pneumonitis have been reported to include the timing and schedule of RT sessions, the mean lung dose, the target volume and dose, pre-existing lung disease, and circulating cytokines. [22][23][24] The risk factors for immunotherapy-related pneumonitis have not been defined; however, suggestions have included active smoking, which we were unable to confirm in our study. 25 Little is known about which risk factors increase the likelihood of irAEs overall and pneumonitis in particular, and what effect irAEs might have on survival.…”
Section: Discussionmentioning
confidence: 67%
“…The risk factors for radiation pneumonitis have been reported to include the timing and schedule of RT sessions, the mean lung dose, the target volume and dose, pre-existing lung disease, and circulating cytokines. [22][23][24] The risk factors for immunotherapy-related pneumonitis have not been defined; however, suggestions have included active smoking, which we were unable to confirm in our study. 25 Little is known about which risk factors increase the likelihood of irAEs overall and pneumonitis in particular, and what effect irAEs might have on survival.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, lower IL8 level was found statistically significant with higher risk of RP2, which is consistent with previous literature on RILT. Both of our previous studies (8,37) and Hart and colleagues (38) had reported that low IL8 was correlated with an increased risk of RILT. IL8 has chemotactic activity for leukocytes and induces collagen synthesis and cell proliferation (39) in animal studies, but it has been consistently found to have an antiinflammatory effect in humans (12,37,38,40).…”
Section: Discussionmentioning
confidence: 79%
“…Both of our previous studies (8,37) and Hart and colleagues (38) had reported that low IL8 was correlated with an increased risk of RILT. IL8 has chemotactic activity for leukocytes and induces collagen synthesis and cell proliferation (39) in animal studies, but it has been consistently found to have an antiinflammatory effect in humans (12,37,38,40). Furthermore, it has been shown that neutrophils penetrate the injury site and perform the critical tasks of dismantling injured vessels and creating channels for new vascular regrowth, which is important for full repair of the sterile injury (41).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It is known that there are remarkable differences between serum and plasma proteomes [17][18][19][20][21]. In the present study, poorly prepared plasma samples (as described above with blood samples either sitting at room temperature or inadequately centrifuged) had a different protein profile from that of good plasma samples (Figure 4).…”
Section: Sample Preparation and Proteomic Profilesmentioning
confidence: 54%